Utilization and Satisfaction of Community-based Health Care Services among Older Adults - Tawacal, Chris Audrey N; Tulaylay, Cassey Angelyn P; Susano, Angelyne Nhicole A; Vergara, Denniese Erin S; Flores, Michael John V (Al-Hijrah Indonesia, 2024)
The COVID-19 pandemic has a significant impact on the capacity of health systems to continue to provide critical services. As healthcare systems around the world face a growing demand for care for patients with COVID-19, it is vital to maintain preventive and curative services, especially for the most vulnerable populations, the elderly and the elderly living with chronic diseases. The purpose of this study was to determine the level of health service utilization and satisfaction of older adults amidst COVID-19 pandemic. The study used a descriptive- correlational research design that was conducted in a selected barangay in the city of Caloocan. The purposive and snowball sampling method was used to select respondents and must meet the following criteria: elderly between the ages of 60 and 74, and using health care services. The data collection was carried out through a series of questionnaires with an informed consent form through online platforms. Based from the data gathered, the strength of the relationship is indicated by the correlation coefficient with a score of. 795, which is greater than 0.70 shows a high correlation between the two variables. This means that when the level of utilization of community-based services of the respondent is high, their level of satisfaction with health care services increases as well. Overall, it is important to prioritize the level of utilization and satisfaction in community-based healthcare among older adults as it is used as an indicator for measuring the quality of healthcare. The level of utilization among older adults is inclined to their level of satisfaction, in which respondents are highly satisfied with their usage of services in terms of accessibility, availability and affordability of the community-based services. Moreover, demographic profile of respondents has no significant difference, which indicates that respondent’s level of satisfaction in community-based services is affected by their level of utilization of services in their barangay health center. Health services, if used by the elderly, can lead to satisfaction. Therefore, the promotion of the various health services is strongly encouraged to reach not only a few, but the whole population.